# Solve the exercise(x+1)(2x-5)=0

*print*Print*list*Cite

### 2 Answers

We have to solve (x+1)(2x-5)=0

x + 1 = 0

=> x = -1

2x - 5 = 0

=> x = 5/2

**The required solution is x = -1 and x = 5/2**

We'll start from the fact that a product is zero if one of the factors is zero.

According to this, the product

(x+1)(2x-5) = 0 if and only if:

x+1 = 0

or

2x - 5 = 0

We'll solve the first equation:

x + 1 = 0

We'll subtract 1:

x = -1

We'll solve the second equation:

2x-5 = 0

We'll add 5 both sides;

2x = 5

We'll divide by 2:

x = 5/2

So, the product is zero if and only if x has the values:

x = -1 or x = 5/2.